Residents' concerns and attitudes toward solid waste management facilities in Palestine a case study of Hebron district - Al-Khatib, Issam A (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2014)
Because of many limitations, the siting, construction and operation of a new solid waste management (SWM) facility is a significant challenge in Palestine. A SWM facility should operate in a sustainable in all aspects, including social acceptance, environmental protection, financial equity, and, in this particular case study, the political acceptance of all regional parts is extremely important. This article presents the outcomes of an extended study that aimed to investigate the concerns and attitudes of the residents of Hebron governorate related to the entire lifecycle of SWM facilities. A structured questionnaire was developed based on literature reviews and was distributed to residents in three different communities in the same governorate with various lifestyle backgrounds. The overall investigation focused on the collection of raw data regarding citizens' levels of concern regarding the environmental impacts of SWM facilities, the general waste management aspects, the benefits gained by the operation of various types of SWM facilities and the attitudes during the construction period of each facility. The results show that concerns about water pollution are significant; the benefits gained as a result of the operation of SWM facilities, particularly the heat supply from incinerators, are welcomed; and 'not in my backyard' syndrome is highlighted. The outcomes of this research are input data for the development of a roadmap that may include educational programs, incentive schemes and active public involvement during all phases of the implementation of SWM facilities (planning, siting, operation), in order to also ensure public acceptance, participation and regional sustainable development